CUSTOMER’S AWARENESS TOWARDS THE ISLAMIC BANKING SYSTEM Case Study on Selected Banking in Duhok City- Kurdistan Region - Jameel, Shivan A. (Humanities Journal of University of Zakho, 2017)
Islamic banking system (IBS) is one of these sectors that affect the economy and it works with free interest rate. This study investigates the level of customer’s awareness toward IBS. The study was conducted on the two Islamic Banks only in Duhok city- Kurdistan Region. The data were collected using structured questionnaire and the sampling was random. Descriptive statistics and Statistical Package Social Science (SPSS V.20) were used to analyze the participants’ responses. The results indicated that customers of Cihan Islamic bank - Duhok and Kurdistan International Bank for Investment and Development are not fully aware of Islamic banking system. Therefore, the study suggests that for Islamic banks to remain active and competitive they need to develop quality-service level in order to supersede the conventional banking standards, invest in new products and services and also develop an effective communication plan by advertising and marketing in order to achieve Islamic customer needs and demands.